2022
DOI: 10.1080/10717544.2022.2081739
|View full text |Cite
|
Sign up to set email alerts
|

Pentapeptide modified ethosomes for enhanced skin retention and topical efficacy activity of indomethacin

Abstract: Challenges associated with topical analgesics and anti-inflammatory drugs include poor drug penetration and retention at the desired lesion site. Therefore, improving these challenges would help to reduce the toxic and side effects caused by drug absorption into the systemic circulation and improve the therapeutic efficacy of topical therapeutic drugs. Pentapeptide (KTTKS) is a signal peptide in skin tissue, it can be recognized and bound by signal recognition particles. In the current study, we successfully p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…77,78 In addition, they can carry a wide range of drugs, including hydrophilic and hydrophobic compounds, making them a versatile drug delivery system. 79,80 They have a high drug-loading capacity, which means that they can carry a large amount of drug per vesicle, that improves the overall efficacy of the treatment and reduces the number of applications needed. 81 Moreover, the ethanol present in ethosomes can help stabilize the vesicles and protect them from degradation.…”
Section: Advantag E S Of E Thosome S Deliverymentioning
confidence: 99%
“…77,78 In addition, they can carry a wide range of drugs, including hydrophilic and hydrophobic compounds, making them a versatile drug delivery system. 79,80 They have a high drug-loading capacity, which means that they can carry a large amount of drug per vesicle, that improves the overall efficacy of the treatment and reduces the number of applications needed. 81 Moreover, the ethanol present in ethosomes can help stabilize the vesicles and protect them from degradation.…”
Section: Advantag E S Of E Thosome S Deliverymentioning
confidence: 99%
“…Lysine-threonine-threonine-lysine-serine is a short signal peptide originated from collagen hydrolysis which interacts with the skin by binding to signal recognition particles present in skin tissue thus improving intradermal drug retention at the lesion site. Skin retention analysis showed that the retention of indomethacin in the skin was 4.51-folds with surface modified ethosomes compared to its plain gel …”
Section: Lipid-based Nanocarrier Systems and The Effect Of Surface Mo...mentioning
confidence: 99%
“…Skin retention analysis showed that the retention of indomethacin in the skin was 4.51-folds with surface modified ethosomes compared to its plain gel. 48 Surface modification can also facilitate synergistic treatment for the management of psoriasis. Guo et al synthesized glycyrrhetinic acid-D-α-tocopherol acid polyethylene glycol succinate (GA-TPGS) to stabilize psoriasis by preventing inflammation and damage by lipid peroxidation.…”
Section: Lipid-based Nanocarrier Systems and The Effect Of Surface Mo...mentioning
confidence: 99%
See 1 more Smart Citation
“…To improve the transdermal penetration and the retention of drugs in the skin, various nanocarriers (such as solid lipid nanoparticles, ethosomes, and emulsions) have been developed to improve topical transdermal delivery ( Ilic et al, 2021 ; El-Hashemy, 2022 ; Niu et al, 2022 ). Among various types of nanocarriers, nanogels have attracted increasing attention due to their unique advantages, including great colloidal stability, tunable size, large surface area for biological coupling, and porous structure for loading large amounts of drugs ( Sivaram et al, 2015 ; Liu et al, 2021a ).…”
Section: Introductionmentioning
confidence: 99%